Study on an Energy-saving Durability Test System for Reciprocating Refrigeration Compressor - Wang Feng; Mi Xiaozhen (Zhileng xuebao)
This paper proposes an energy-saving system which is used to test the reliability of reciprocating refrigeration compressor. This system is established based on the principle of condensing of the partial refrigerant with high temperature and high pressure. The condensed refrigerant and the uncondensed refrigerant are mixed into a saturated vapor entering the suction of the compressor. The refrigerant mass flow of the condensed and the uncondensed are calculated. The result indicates that only a small fraction of refrigerant is needed to be condensed and the selection of a condenser with small power can satisfy the experiment requirements. The proposed system is built and its availability is testified by carrying out the durability test of a reciprocating compressor, which shows this test system is featured with simple, energy-saving and low cost.